Chemoselective N−H insertion catalyzed by a de novo carbene transferase. (22nd May 2020) - Stenner, Richard; Anderson, John Leslie Ross
Abstract: The ability to perform organic reactions with chemoselectivity is of critical importance in synthesis. Recently, we reported that a de novo carbene transferase, a tetra‐α‐helical c ‐type heme‐containing protein, C45, is proficient at N−H insertion reactions, proceeding via the intermolecular transfer of a metallocarbenoid intermediate into the N−H σ‐bond to form a new N−C σ‐bond. Here we demonstrate that C45 can also catalyse N−H insertion reactions chemoselectively, even when the substrate contains an unprotected hydroxyl group. Abstract :